Prevalence and molecular characterization of canine parvovirus-2 in dogs in Giza Governorate, Egypt - Mekky, Reham H.; Shoulah, Salma; Moustafa, Abdelmoneim; Selim, Abdelfattah; Marawan, Marawan A. (Journal of Advanced Veterinary Research, 2024)
Canine parvovirus type-2 (CPV-2) is one of the most common diseases affecting dogs. The disease has been reported worldwide including Egypt causing both acute hemorrhagic enteritis and myocarditis in the infected dogs. Two distinct parvoviruses are incriminated in the disease occurrence CPV-1 and CPV-2. However, the CPV-2 is the most pathogenic and includes three antigenic variants namely, CPV2a, CPV2b and CPV2c. Since the molecular characterization of CPV is critical for future disease prevention and control, the current study aimed to determine the prevalence of CPV-2 in dogs in Giza governorate, Egypt, and molecular characterization of circulating CPV-2. A total of 300 stool samples were collected from dogs with clinical signs suggestive of canine parvovirus from different veterinary hospitals and clinics in Giza governorate, during the period from January 2022 to December 2022. The overall prevalence of CPV-2 in dogs was 72.67% and it was significantly associated with breed, sex and age of examine dogs. In addition, the sequencing and phylogenetic analysis of circulating CPV-2 based on VP2 gene revealed that the circulating strain is CPV-2c. The present findings suggest that the failure of vaccination may be attributed to the use of CPV-2b commercial vaccines in areas where CPV-2c is prevalent.